A COMPARATIVE STUDY OF SPEAKING SKILLS BETWEEN STUDENTS’ WITH HIGH AND LOW LEVELS OF NEUROTICISM - Maharani, Deswita Aulia; Dewi, Desi Surlitasari; Adam, Adam (IAIN Syekh Nurjati Cirebon, 2025)
This study investigated the differences in speaking skills between students with high and low levels of neuroticism using a sequential explanatory mixed methods design with comparative approach. The research involved 41 senior high school students from SMA Muhammadiyah Batam who completed neuroticism assessments using adapted NEO-FFI questionnaire and speaking performance tests. Quantitative analysis through Independent Sample T-Test revealed statistically significant differences (p < 0.001) in speaking scores between high and low neuroticism groups, with low neuroticism students achieving higher performance. Qualitative interviews with selected participants were analyzed using thematic analysis, revealing three main themes: speaking anxiety, coping strategies, and motivation and learning attitudes. While low neuroticism students employed a variety of informal methods of learning and reacted positively to feedback, high neuroticism students showed more speaking anxiety, employed less efficient methods of preparation, and had more self-doubt. These results have practical implications for EFL teacher and advance our understanding of the links between personality and language learning within the Big Five framework. The findings highlight how crucial it is to take individual personality characteristics into consideration when creating speaking curriculum and putting classroom strategies into practice in order to maximize learning outcomes for each individuals.